2012
DOI: 10.1038/npp.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cues Reinstate Cocaine-Seeking Behavior and Induce Fos Protein Expression as Effectively as Conditioned Cues

Abstract: Cue reinstatement of extinguished cocaine-seeking behavior is a widely used model of cue-elicited craving in abstinent human addicts. This study examined Fos protein expression in response to cocaine cues or to novel cues as a control for activation produced by test novelty. Rats were trained to self-administer cocaine paired with either a light or a tone cue, or received yoked saline and cue presentations, and then underwent daily extinction training. They were then tested for reinstatement of extinguished co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…In the absence of this dopaminergic challenge, short-access meth rats respond equally for the novel vs meth cue on the novel cue relapse test. This finding is consistent with a study by Bastle et al, (2012), who reported that short-access (2 h daily self-administration sessions for 2 weeks) cocaine rats respond equally for novel and cocaine cues on a reinstatement test conducted after two weeks of extinction training. In the latter study, however, the novel and cocaine cues were tested in separate animals, so this model did not address the ability of novel cues to compete with conditioned drug cues in a choice setting.…”
Section: Novelty Detection Vs Novelty Rewardsupporting
confidence: 92%
“…In the absence of this dopaminergic challenge, short-access meth rats respond equally for the novel vs meth cue on the novel cue relapse test. This finding is consistent with a study by Bastle et al, (2012), who reported that short-access (2 h daily self-administration sessions for 2 weeks) cocaine rats respond equally for novel and cocaine cues on a reinstatement test conducted after two weeks of extinction training. In the latter study, however, the novel and cocaine cues were tested in separate animals, so this model did not address the ability of novel cues to compete with conditioned drug cues in a choice setting.…”
Section: Novelty Detection Vs Novelty Rewardsupporting
confidence: 92%
“…For example, electric footshock increases Fos expression in several stress- and reward-related brain regions to significantly greater levels in rats with a history of ethanol self-administration than in ethanol-naïve rats ( Zhao et al, 2006 ). This is further supported by studies examining cue-induced reinstatement, in which animals with a history of cocaine SA display higher cue reactivity, as assessed by greater Fos activation, in several key brain regions, than drug-naïve animals ( Bastle et al, 2012 ; Kufahl et al, 2009 ). The effects of prior drug exposure on stressor-induced Fos responses also appears to be brain region-dependent.…”
Section: Stress-associated Neurocircuitry: Evidence From Fos Imagingmentioning
confidence: 75%
“…perirhinal cortex may integrate emotional and sensory information before it is conveyed to the hippocampus (Kajiwara et al 2003). Interestingly, novel cues were found to be as effective at triggering reinstatement as cocaine conditioned cues, and both types of cues activated a common neural circuit, measured by Fos expression (Bastle et al 2012). Given that our relapse model incorporates competition between novel cues and conditioned meth cues, the BLA could provide a critical input to the perirhinal cortex conveying the emotional significance of the meth cues, allowing the competition between meth and novel cues within the perirhinal cortex to be computed at a synaptic level before the outcome is relayed to the hippocampus.…”
Section: Discussionmentioning
confidence: 99%